Glycyrrhizin for treatment of CRS caused by CAR T-cell therapy: A pharmacological perspective - Qi, Xingxing; Li, Juan; Luo, Pan (Frontiers in Pharmacology, 2023)
Chimeric antigen receptor T (CAR-T) cell therapy has the promise to revolutionize the management of hematologic malignancies and possibly other tumors. However, the main side effect of cytokine release syndrome (CRS) is a great challenge for its clinical application. Currently, treatment of CRS caused by CAR-T cell therapy is limited with tocilizumab (TCZ) and corticosteroids in clinical guidelines. However, the theoretical risks of these two agents may curb clinicians’ enthusiasm in application and the optimal treatment is still in a matter of debate. CAR-T cell therapy induced-CRS treatment has been the one of the research focus nowadays. Glycyrrhizin, which has multifarious pharmacological effects, good tolerance and affordability, is an ideal therapeutic alternative for CRS. It can also overcome the shortcoming of TCZ and corticosteroids. Therefore, in this brief article we discussed the therapeutic potential of glycyrrhizin for the treatment of CRS caused by CAR-T cell therapy from the perspective of its pharmacological action.